2011
DOI: 10.1007/s00223-011-9524-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Wall–Derived Endothelial Colony-Forming Cells Enhance Fracture Repair and Bone Regeneration

Abstract: Endochondral bone formation requires new blood vessel formation, and endothelial progenitor cells (EPCs) may play a role in this process. Endothelial colony-forming cells (ECFCs), one subtype of EPCs, isolated from the microvasculature of rat lungs, exhibited cell surface antigen markers and gene products characteristic of endothelial cells and displayed high proliferative potential and an ability to form vessel-like network structures in vitro. The aim of this study was to evaluate whether ECFCs facilitate bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…However, in the future, these HAP-GEL constructs may require loading of endothelial progenitor cells to generate microvascularization and promote a faster regeneration. 9 In conclusion, the fabrication of a rigid macroporous TiO 2 -enriched HAP-GEL scaffold was found feasible for bone regeneration applications in calvaria defects. After 12 weeks postimplantation, TiO 2 -HAP-GEL scaffolds loaded with ODMAPCs promoted osteointegration, NFB in the macroporous areas and significantly enhanced bone regeneration.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, in the future, these HAP-GEL constructs may require loading of endothelial progenitor cells to generate microvascularization and promote a faster regeneration. 9 In conclusion, the fabrication of a rigid macroporous TiO 2 -enriched HAP-GEL scaffold was found feasible for bone regeneration applications in calvaria defects. After 12 weeks postimplantation, TiO 2 -HAP-GEL scaffolds loaded with ODMAPCs promoted osteointegration, NFB in the macroporous areas and significantly enhanced bone regeneration.…”
Section: Discussionmentioning
confidence: 84%
“…This poor collagen-related effect has been recently reported at CSD in rat fibulas. 9 In this latter report, researchers found that cellfree collagen sponges have a very limited microvascular network in both fracture healing and CSD models, unlike HAP-based constructs. 9 Results found here with the implanted cell-free TiO 2 -HAP-GEL were further confirmed within the undecalcified sections with NFB-specific staining and after evaluating the MAR.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Regardless of where the circulating EPCs originated, frequency of EPCs in PB or BM is known to be extremely low [6,8,17,[20][21][22][23]. Other studies using rat lung tissues or human renal arteries have shown success in isolating functional ECFCs, but it will be difficult to translate the same approaches to clinical settings [24,25].…”
Section: Cd133mentioning
confidence: 99%